EVALUATION OF REACTOGENICITY, SAFETY AND IMMUNOGENICITY OF INACTIVATED MONOVALENT VACCINE IN CHILDREN - A.N. Mironov; A.A. Romanova; R.Ya. Meshkova; I.V. Fel'dblyum; N.V. Kupina; D.S. Bushmenkov; A.A. Tsaan ("Paediatrician" Publishers LLC, 2010)
NPO «Microgen» developed vaccine «PANDEFLU» - influenza inactivated subunit adsorbed monovalent vaccine, strain A/California/7/2009 (H1N1), for specific prophylaxis of pandemic influenza in different age groups of citizens. Reactogenicity, safety and immunogenicity were analyzed in a study of volunteers 18-60 years old. The article presents results of administration of vaccine «PANDEFLU» in children. The study performed in two clinical centers proves good tolerability, reactogenicity, safety and high immunogenicity of this vaccine.Key words: children, influenza, influenza virus А/H1N1, inactivated influenza vaccine, reactogenicity, safety, immunogenicity.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(4):106-109)